Yeast and bacteria co-culture-based lipid production through bioremediation of palm oil mill effluent: a statistical optimization - Karim, Ahasanul; Islam, M. Amirul; Mishra, Puranjan; Abu Jafar, Md Muzahid; Yousuf, Abu; Rahman Khan, Md. Maksudur; Che Ku, Mohammad Faizal (Springer, 2021)
In the present study, a co-culture of yeast (Lipomyces starkeyi) and bacterium (Bacillus cereus) was used to optimize lipid accumulation capability and simultaneous treatment of wastewater using palm oil mill effluent (POME) as a carbon source. The influence of process parameters (i.e., inoculum composition, pH, temperature, and time) on the lipid accumulation and the chemical oxygen demand (COD) removal were optimized using design of experiments (DoE) as a statistical tool. The DoE results suggested that the maximum lipid accumulation of 2.95 g/L and COD removal efficiency of 86.54% could be obtained while the inoculum composition, pH, temperature, and incubation time were 50:50, 6.50, 32.5 °C, and 90 h, respectively. The predicted results were very close to the experimental results (< 5% deviation); hence, the proposed model could be useful to predict the lipid accumulation and COD removal performance of a yeast and bacteria co-culture.